ANALISIS IMPLEMENTASI KEBIJAKAN PEMUNGUTAN PAJAK HIBURAN UNTUK MENINGKATKAN PENERIMAAN PAJAK DAERAH PADA SUKU BADAN PAJAK DAN RETRIBUSI DAERAH KOTA ADMINISTRASI JAKARTA SELATAN TAHUN 2016-2018 - Puspita, Lidya Tri; Dewanti, Yopy Ratna (JURNAL LENTERA AKUNTANSI, 2024)
The objective of this study is to find out the implementation of Entertainment Tax Collection at the Local Tax and Retribution Agency of South Jakarta. This study used Van Meter and Van Horn theories. Entertainment Tax is any of potential sources of local income for high funds from the Indonesian Citizen bearing tax obligations. Besides, it also any of efforts in optimizing local tax revenue. This study used a descriptive qualitative research method. Result of the study identified that between year 2016-2018 the Entertainment Tax Revenue in South Jakarta experienced decrease every year. There are some obstacles in Entertainment Tax Collection and Control. So, it requires a number of steps should be taken to cope with such obstacles. Keywords: Policy Implementation, Entertainment Tax, Local Tax Revenue